E-books as Digital Learning Resources in Higher Education: A Systematic Literature Review - Muhammad Hardi HR; Besse Wahida (Actual Insight, 2026)
Advances in educational technology have prompted higher education institutions to make adjustments to their learning systems, including the adoption of e-books as learning resources. This study analyzes how e-books are used as digital learning resources in higher education institutions using qualitative methods through a systematic literature review approach. The focus of this research includes the following sub-topics: 1. the conception of e-books as learning resources in higher education institutions. 2. The characteristics of e-books as learning resources, and 3. The relevance of e-books to learning needs in higher education institutions. The concept of e-books as digital resources is an evolution of traditional printed books that are transformative by integrating various multimedia elements with PDF, EPUB, or MOBI formats that enable cross-platform compatibility and ease of distribution via the internet. E-books occupy a highly strategic position within the learning resources ecosystem because their nature allows for real-time updates. The characteristics of e-books as learning resources include portability, interactivity, and flexibility. The relevance of e-books to learning needs in higher education is demonstrated by their alignment with students’ learning styles such as visual, auditory, and kinesthetic as well as students’ tendency to use mobile devices. With these characteristics, e-books serve as a learning medium that addresses various challenges in traditional classroom instruction. Their presence is central and significant in enhancing digital systems and the quality of learning in higher education.